Pengaruh Disiplin Kerja, Kompensasi, Motivasi Kerja Terhadap Kinerja Karyawan pada Solo Techno Park Surakarta - Fedyana Wahyu Widjaya; Triyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study examines how work discipline, compensation, and motivation affect employee performance at Solo Techno Park in Solo, Indonesia. The study used a purposive sampling technique with a sample size of 96 people. It targets all employees. Data were collected quantitatively using techniques such as Instrument Requirements Test, Classical Assumption Test, and Hypothesis Test using SPSS. The results show that work discipline significantly improves performance, with a t-test value of 3.861 and a p-value of 0.000 indicating a strong correlation. Compensation also has a positive impact on performance, with a t-test value of 2.160 and a p-value of 0.033. However, with a t-test value of 18.053 and a p-value of 0.000, work motivation turned out to be the most important, with 83% of the variation in employee performance. Regression analysis shows that these three factors are responsible for 83% of the variation in employee performance, indicating that employees must be disciplined, fairly rewarded, and motivated to achieve optimal results.